2016
DOI: 10.1177/0748233715571152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetylcysteine administration on homocysteine level, oxidative damage to proteins, and levels of iron (Fe) and Fe-related proteins in lead-exposed workers

Abstract: N-Acetylcysteine (NAC) could be included in protocols designed for the treatment of lead toxicity. Therefore, in this study, we decided to investigate the influence of NAC administration on homocysteine (Hcy) levels, oxidative damage to proteins, and the levels of iron (Fe), transferrin (TRF), and haptoglobin (HPG) in lead (Pb)-exposed workers. The examined population (n = 171) was composed of male employees who worked with Pb. They were randomized into four groups. Workers who were not administered any antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
15
1
1
Order By: Relevance
“…All studies of this review support that Pb concentrations are correlated with high levels of Hc [9,[21][22][23][24][25][26][27][28][29][30].…”
Section: Lead (Pb)mentioning
confidence: 69%
See 4 more Smart Citations
“…All studies of this review support that Pb concentrations are correlated with high levels of Hc [9,[21][22][23][24][25][26][27][28][29][30].…”
Section: Lead (Pb)mentioning
confidence: 69%
“…In studies describing workers exposed to Pb [9,24,26], the levels of Hc were slightly higher than in the general population and confirmed that Pb blood levels were associated with high Hc levels. Kasperczyk et al [24] reported that Pb decreases levels of GSH and protein thiol groups. Pb-induced oxidative stress contributes to the increase in protein carbonyl groups.…”
Section: Lead (Pb)mentioning
confidence: 82%
See 3 more Smart Citations